Handgrip strength reference intervals in Swedish, young, healthy adults: The LBA study - Pettersson-Pablo, Paul; Nilsson, Torbjörn K.; Hurtig-Wennlöf, Anita (Nutrition (Burbank, Los Angeles County, Calif.), 2023)
•Handgrip strength may differ strongly between populations•Reference intervals are best established locally•Sex, height, and fat-free mass are the main determinants of hand-grip strength Handgrip strength (HGS) is a surrogate marker of general risk and nutritional status, frequently used in clinical practice. This study aimed to determine clinically useful reference intervals for healthy, young adults from Northern Europe. This cross-sectional study was conducted in central Sweden, recruiting 834 young, nonsmoking adults ages 18 to 26 y. Subjects responded to a questionnaire on general health status, medication (including contraceptives), exercise habits, and parental and their own country of birth. Anthropometry, bioimpedance analysis for determination of fat-free mass (FFM), and HGS was measured. Reference intervals were calculated as mean and standard deviation. Differences between men, women, and women using estrogen contraceptives were analyzed using an analysis of variance with Tukey's post hoc test. Associations between HGS and determinant variables were analyzed using Spearman and linear regressions. Men and women differed in HGS, but no significant difference was found in average HGS based on contraceptive use in women. Mean HGS was 53 kg in men and 34 kg in women, with a range of 22 kg to 90 kg in men and 16 kg to 73 kg in women. Height correlated with HGS. Subjects with a body mass index (BMI) <20 had statistically significantly lower HGS than those in higher BMI groups. There was no statistically significant mean difference between the group of subjects with a BMI of 20 to 25 and those with BMI >25 in neither men nor women. HGS in both sexes showed a gradual increase through tertiles of FFM. In linear regression models, sex, height, and FFM were the main determinants of HGS. In this study, we established reference intervals for HGS in healthy Swedish adults ages 18 to 26 y. As a surrogate marker of whole-body muscle mass, these reference intervals can be used in health assessments and the planning of health-promoting measures in the individual young adults. Differences in HGS based on height warrant height-specific reference intervals that should be established locally.